1971
DOI: 10.2466/pr0.1971.29.3.771
|View full text |Cite
|
Sign up to set email alerts
|

Role of Stimulus Generalization in the Treatment of Alcoholism

Abstract: 7 avoidance and 6 escape Ss were conditioned to an alcoholic beverage and administered the Rotter internal vs external locus of control of reinforcement test. 23 Ss, all patients at the Sepulveda V.A. Hospital, were tested for generalized conditioned anxiety in reaction to other alcoholic beverages after acquisition and extinction procedures. Results (χ3) showed significant generalization for all experimental Ss combined in extinction who externalized their locus of control of reinforcement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
1983
1983

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Further findings suggest that when Ss who value internal locus of control are placed in situations which allow no opportunity for internal control they frequently manifest behavior which may be conceptualized as "reactance" or "resistance" {Brehm, 1966). Cohen and Phelan (1971) demonstrated that "internal" alcoholics showed rapid extinction following aversive conditioning, whereas "external" alcoholics showed both generalization of an "anxiety" response across various alcoholic stimuli, and a prolonged extinction process.…”
Section: And Grings {1973)mentioning
confidence: 98%
“…Further findings suggest that when Ss who value internal locus of control are placed in situations which allow no opportunity for internal control they frequently manifest behavior which may be conceptualized as "reactance" or "resistance" {Brehm, 1966). Cohen and Phelan (1971) demonstrated that "internal" alcoholics showed rapid extinction following aversive conditioning, whereas "external" alcoholics showed both generalization of an "anxiety" response across various alcoholic stimuli, and a prolonged extinction process.…”
Section: And Grings {1973)mentioning
confidence: 98%